Asymmetric Information And Farmer’s Participation In Tobacco Contract Farming - Rondhi, Mohammad; Imelda, Sisca; Setyawan, Hendrik; Aji, Joni Murti Mulyo; Hariyati, Yuli; M, Mustapit; Raharto, Sugeng; Fauziah, Diana; Kusmiati, Ati (Universitas Negeri Semarang, 2020)
Contract farming (CF) is an important tool to initiate structural transformation of agricultural sector in developing countries. However, one of pertinent problems in its establishment is asymmetric information. This problem creates a condition of mutual distrust between the contracting parties and decreases farmer’s participation in it. Thus, this study aimed to explain the asymmetric information problem in CF and find the correlates of farmer’s participation in it. As one of important industrial crops, this study focused on tobacco CF. This study was conducted at two villages (Antirogo and Nogosari) on two different sub-district (Sumbersari and Rambipuji) in Jember. A sample of 113 farmers were interviewed to collect the data. A descriptive analysis was used to explain the contract arrangement and asymmetric information in tobacco CF. A probit estimation was used to identify the coorelates of farmer’s participation in tobacco CF. The results showed that asymetric information does exists in tobacco CF and can be minimized through intense monitoring and increased transparancy. Both of these are possible when the company contracting directly with farmers. Meanwhile, younger farmer and those with more land are more likely to participate in CF. Furthermore, participation in CF is highly correlated with the increases in farm income. Finally, policy aimed to fostering CF should focused more on regulation that minimize the transaction cost of CF. In addition, in the long term, the policy should focused on incentivize young farmers and encouraging youth to enter agriculture.